Transient voltages and energy balance in REBCO insulated magnet: experimental and numerical studies. (30th September 2021) - Vialle, Julien; Badel, Arnaud; Rozier, Blandine; Tixador, Pascal
Abstract: Different means are investigated today to protect a rare earth–barium–copper oxide (REBCO) coil against local thermal runaway, what is commonly called a 'Quench'. Metal Insulated Coil or No-Insulated coil have been successfully introduced. However, these protections method may show other issues and are limited in terms of dynamics, making them impractical for fast applications. We successfully tested early detection of dissipative voltage followed by current dumping as a method to protect REBCO insulated test coils, even with engineering current density in the kA mm −2 range. Pick up coils can be used to compensate inductive coil voltage. In previous works we highlighted the presence of transient voltage due to the hysteretic current distribution in REBCO tape width, which can complicate the detection. We then developed a numerical electromagnetic model that reproduce the transient behavior of REBCO coils. Here we study a small REBCO coil instrumented with three different pick-up coils, including a co-wound pick-up whose coupling is close to perfect. The post processing and analysis of the simulation results makes it possible to identify in the transient coil voltage the contribution due to transient losses and coil inductance variation. The resulting evaluation of the REBCO coil inductance and its variations is validated by analysis of the pick-up coil signals. From a practical point of view, this work shows the possibility to have very sensitive early detection of thermal runaway if the threshold is adjusted based on the expected coil compensated voltage drift. The interest of using isolated high-strength co-wound reinforcement tape as pick-up coil is also highlighted.